Late Quaternary Land Emergence in Northern Ungava, Quebec - Matthews, Barry (ARCTIC, 1967)
Twenty-one C14 dates of material from Late Quaternary marine terraces are used to construct an isostatic uplift curve. The phase of rapid uplift averaged about 26 ft. per 100 years, while for the past 5,200 years uplift was just under 1 ft. per 100 years. Updoming resulted in an upward (southerly) tilt of the "Glacier Beach" (460-ft. strandline) and "Upper Tunit Beach" (100-ft. strandline) at about 5.6 ft. per mile and 3.6 ft. per mile respectively. The C14 dates indicate that the general deglaciation of northern Ungava occurred about 7,000 to 8,000 years ago. Twelve well-formed marine terraces have been identified at the heads of the major fjords. The fauna of the "Upper and Lower Aporrhais Beaches" (40 ft. and 55 ft. strandlines) suggests that optimal marine conditions occurred about 3,900 to 5,230 radiocarbon years ago during a possible marine transgression. Hydroclimatic conditions during the formation of Aporrhais deposits in Sugluk Inlet (62°10'N.) corresponded to those at 58°15'N. Relèvement du sol au Quarternaire récent dans le nord de l'Ungava, Québec. Pour construire une courbe de relèvement isostatique, l'auteur utilise 21 datation au C14 se rapportant à des terrasses marines. Le relèvement, dans sa phase la plus rapide, atteignit en moyenne 26 pieds (7,93 m) par siècle; cependant au cours des 5,200 dernières années, il s'est situé juste au-dessous d'un pied (30 cm) par siècle. Le bombement a provoqué un pendage vers le sud de la "plage Glacier" (plage soulevée à 460 pieds—140,3 m) et de la "plage Tunit supérieure" (plage soulevée à 100 pieds—30,5 m) d'environ 5,6 pieds au mille (1 m/km) et 3,6 pieds au mille (60 cm/km) respectivement. Les radio-datations indiquent que la déglaciation générale du nord de l'Ungava se produisit il y a environ sept à huit millénaires. A la tête des grands fjords, on a identifié douze terrasses marines bien développées. La faune des "plages Aporrhais supérieure et inférieure" (plages oulevées à 40 pieds—12,20 m—et à 55 pieds—16,76 m) suggère que les conditions marines ...